“Please stop calling me a Koreaboo”: stereotyping learners of Korean as a foreign language and its impact on language learning anxieties - Lau, Josephine Faith Hiu Yung (Nanyang Technological University, 2023)
Foreign Language learning anxieties (FLLA) tend to impede a learner’s acquisition of the target language and reduce their willingness to communicate (WTC). With the ubiquity of Korean pop culture now influencing more people to learn Korean as a foreign language (KFL), stereotypes surrounding KFL learners have grown. These negative impressions also pose threats to KFL learners’ anxiety levels. This present study hence investigates the effects of such stereotypes on KFL learners’ FLLA and WTC. A mixed-methods survey was used to collect data on 50 intermediate KFL learners. Adapted versions of Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale and Kim, Zhao and Diskin-Holdaway’s (2022) WTC survey were used to study participants’ FLLA and WTC, alongside questions which surveyed participants for their past experiences of being stereotyped. Follow-up interviews were thereafter held to understand participants’ affective states more deeply. Findings from this research show that the relationship between a learners’ experience of being stereotyped and their FLLA levels is not strictly negative. While higher-anxiety participants showed significant correlations between their experiences of being stereotyped and FLLA levels (r=.54, p<.01), lower-anxiety participants showed no significant correlation (r=-.33, p=.124). Subsequently, correlations between participants’ FLLA levels and WTC in Korean were found to be generally non-significant. Evidence that individual dispositions have an important role to play in mediating learners’ responses to negative experiences was also revealed through this research, suggesting that learners react differently to being stereotyped because of their character.